CAMINHO DA ÁGUA - DIÁLOGO ENTRE O RIO TIETÊ E O CENTRO HISTÓRICO DE SANTANA DE PARNAÍBA - Ximenes, Deize (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The current city model is developing in a hostile environment, where the man turns the natural environment into function of his economical and political interests, and like consequence, is losing the bond with the history and the culture of his city, produced along the time for the humanization of the landscape. So, this research aims to propose guidelines for a sustainable urban project for the Historical Center of Santana de Parnaíba, from the increase in value of the ecological structure and of the cultural structure, rescuing the identity and the culture of society, intensifying the man - nature relationship and providing a better quality of life.